Pendidikan Kristen dalam Keberhasilan Moral Kerohanian Anak di Keluarga - Debora Pandanan; Rahmat Kristiono (Sekolah Tinggi Teologia Kerusso Indonesia, 2022)
Moral education is the basic values and character needed in every aspect of a child's life, especially within the child's family environment. Parents play a significant role in the spiritual growth of each of their children in everyday life. Knowledge of Christian spiritual education for children is essential because even in the Bible, God commands humans to teach the word of God, especially to children. Using a descriptive qualitative method, this research discusses and concludes that parents should wholeheartedly support their children so that their spiritual life grows daily because the spiritual growth that a child will experience is very dependent on Christian education in the family. Second, a parental example to children is one factor that plays a vital role in Christian Religious Education.